Comparison of chest X-ray with lung ultrasound in the diagnosis of pneumonia in children aged 02 months to 12 years - Mudassar Sharif, Tariq Saeed, Khalid Saheel, Khushdil Khan, Muhammad Hussain, Abid Hussain, Mudassar Sharif, Tariq Saeed, Khalid Saheel, Khushdil Khan, Muhammad Hussain, Abid Hussain (Journal of Rawalpindi Medical College, 2021)
Objective: To observe the reliability of lung ultrasound in diagnosing pneumonia as compared to chest X-ray. Materials and Methods: This Prospective cohort study was carried out over a period of three months in the Paediatric Department of Benazir Bhutto Hospital Rawalpindi. One hundred patients, 2 months to 12 years of age were enrolled in the study. All the patients were subjected to chest X-ray and lung ultrasound within 12 hours of admission. Data was recorded on predesigned Performa and processed on SPSS version 25. Sensitivity, specificity, positive and negative predictive values were calculated for chest X-ray and lung ultrasound. Results: LUS was found to be more efficient in detecting consolidations (64 out of 100) as compared to CXR (50 out of 100). In 14 patients CXR was not able to detect consolidations but LUS detected the same. Fourteen patients in whom lung ultrasound was positive for consolidations but CXR was negative were subjected to CT chest. Out of these 14 CT scans, 11 were positive and 3 were negative for consolidations. Lung ultrasound was found to have a Sensitivity of 100%, the specificity of 92.30%, PPV 95.31%, NPV of 100%, and accuracy of 97% as compared to Sensitivity of 81%, the specificity of 100%, PPV 100%, NPV of 78% and accuracy of 89% for CXR in the diagnosis of pneumonia in children. Conclusion: Results from our study confirmed by many other studies on the same research question allow us to conclude that Lung ultrasound is a fast, low cost, reliable, radiation-free alternative to chest x-ray in the diagnosis of pneumonia in children.